The Accuracy of Immunoscore and Neutrophil Lymphocyte Ratio in Predicting 5 years Recurrence of Stage I-III Colorectal Cancer - Kristianto, Yusak; Jeo, Wifanto Saditya (http://dharmais.co.id/, 2025)
Background: It is estimated about 30-50% of colorectal cancer (CRC) patients experience recurrence even after definitive therapy. Immune-based tests, such as immunoscore (IS) and Neutrophil-Lymphocyte Ratio (NLR) are independent predictors of CRC recurrence and survival. NLR examination is more affordable, simple, and feasible compared to oncological panel examination IS. To this date, there have been no studies measuring the accuracy of both in predicting recurrence rates in CRC.Methods: This retrospective cohort study was conducted at Siloam Kebon Jeruk Hospital and Mochtar Riady Comprehensive Cancer Centre (MRCCC) from July to December 2023, utilizing secondary data from medical records of stage I-III CRC patients, focusing on NLR and IS results, and outcomes. Statistical analysis comprised descriptive analysis, accuracy test, and hypothesis testing (bivariate) using the Statistical Package for the Social Sciences (SPSS) version 25. NLR cut-off value was computed using the ROC curve. The comparison of NLR and IS test values was assessed through a comparison of ROC area (AUC). Measure of agreement between the two tests (NLR and IS) was done using Kappa statistics.Results: Out of 80 CRC patients, 26 patients experienced recurrence (32.5%), mostly in the first two years (53%), while 54 patients did not recur (67.5%). NLR (cut-off 6.6) showed sensitivity (46.2%), specificity (81.5%), and diagnostic accuracy value of 70%. Chi-square analysis indicated a significant relationship between NLR and recurrence (p-value = 0.020). IS showed sensitivity (7.7%), specificity (96.3%), and diagnostic accuracy value of 67.5%. Fisher’s Exact analysis showed no significant relationship between IS and recurrence (p-value = 0.592). The AUC value of both tests indicated that the accuracy to predict recurrence in CRC patients is not different/ same (p-value = 0.064). The Kappa statistic indicates a very high agreement between high IS and low NLR tests in predicting recurrence cases (p-value = 0.001).Conclusions: NLR and IS have the same weak accuracy in predicting stage I-III CRC recurrences, but NLR has a statistically significant association compared to IS. A combination of both tests showed a strong predictive role in tumor recurrence after curative surgery and can be applied in daily practice (postoperative surveillance).